Lead Ion Detection in Challawa Water: Development and Application of Response Surface Methodology (Journal of Environmental Bioremediation and Toxicology, 2024)
Agricultural areas in Nigeria depend upon unpolluted water sources and hence need continuous monitoring. River Challawa is among the water sources for domestic and agricultural purposes. It is located in an industrialized area of Kano, Nigeria. A cucumber protease-based assay for the detection of lead metal has been developed to determine the efficiency of the monitoring method. Cucumber protease is assayed by using casein as a substrate with Coomassie brilliant blue to track the complete hydrolysis of the substrate. In the presence of inhibitors such as metal ions, casein is not hydrolyzed to completion, and the solution is dark blue. The cucumber protease assay was optimized using One-Factor-at-a-Time (OFAT) and Response Surface Methodology (RSM). The RSM-optimized method demonstrated superior sensitivity, reducing the IC50 value for lead detection from 0.078 mg/L (OFAT) to 0.028 mg/L. The findings show a marked improvement in concentration, causing 50% inhibition ( IC50) for lead metal in River Challawa. The results of the comparison between one factor at a time (OFAT) optimization and RSM provide an improvement of  IC50 for lead ion from 0.078 (95% CI,0.057 to 0.27) to 0.028 (95% CI, 0.022 to 0.037). The LOD for lead Pb2+ is 0.015 and 0.003 for OFAT and RSM, respectively. The results of this study indicate that cucumber-protease assay has the potential efficiency of being used in the determination of lead metal in water samples.
Keywords: Cucumber protease; Inhibitive assay; Lead; Coomassie dye-binding assay; River Challawa